2009
DOI: 10.1016/j.transproceed.2009.01.074
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hepatitis B and C Virus Infections on Kidney Transplantation: A Single Center Experience

Abstract: Objective. The impacts of hepatitis C virus (HCV) and hepatitis B virus (HBV) infections on patient and renal graft survivals are controversial. This study sought to evaluate the effects of pretransplantation HCV and HBV infections on renal transplant patients and their grafts at our center. Patients and Methods. We retrospectively examined 1224 renal transplantations performed between 1992 and 2006, including 28 HBsAg positive; 64, anti-HCV; 9, anti-HCV plus HBsAg positive; and 1123, negative for anti-HCV and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 15 publications
2
21
0
1
Order By: Relevance
“…While some studies reported an increased rate of rejection (20,21), others concluded that there was no significant difference (22). In our study, there were similar overall rates of rejection episodes in the anti-HCV-positive and -negative groups.…”
Section: Parameters Hcv (+) (N=100) Hcv (-) (N=1711) P Valuesupporting
confidence: 68%
See 1 more Smart Citation
“…While some studies reported an increased rate of rejection (20,21), others concluded that there was no significant difference (22). In our study, there were similar overall rates of rejection episodes in the anti-HCV-positive and -negative groups.…”
Section: Parameters Hcv (+) (N=100) Hcv (-) (N=1711) P Valuesupporting
confidence: 68%
“…Hepatitis C virus and renal transplantation 169 survivals (1,16,22). Our study revealed that there was no difference in patient survival between anti-HCV-positive and -negative groups over the 10-year study period, but graft survival was shorter in the 10 th year in the anti-HCV-positive group.…”
Section: Parameters Hcv (+) (N=100) Hcv (-) (N=1711) P Valuementioning
confidence: 53%
“…In developed countries around 1.8 to 8% of renal transplant patients are infected with HCV [1,2]. Indeed, prior to the era of the new direct acting antivirals (DAAs), the treatment of hepatitis C was based solely on the combination of standard interferon and ribavirin.…”
Section: Commentarymentioning
confidence: 99%
“…Pre-therapy HBV DNA was 6.3 and 8.68 Log 10 Eq/mL by branched DNA assay (bDNA assay) respectively, with detectable HBeAg in serum. ADV-based therapy was given for a median time of 15 months (range = [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. A significant reduction of serum HBV DNA occurred without changes in the HBeAg serologic status.…”
Section: Therapy Of Hepatitis B In Dialysis Patients: Adefovirmentioning
confidence: 99%